Effectiveness of Street Children Handling Policy amid Urban Spatial Inequality: A Case Study in Makassar City, Indonesia - Pratama, Galank; Al Khaer Zahir, Muh. Zuhud; Alan Syahrier , Fajar; Anshori , M. Wira; Astuti, Widya (Golden Ratio of Data in Summary, 2025)
This research discusses the phenomenon of street children in Makassar City through a political sociology approach and Henri Lefebvre's theory of space production. The research identifies the causes of street children's emergence and analyzes the government's countermeasures. Massive urban development by the government and capitalists has created social inequality, dividing urban space into abstract space, which the state and capital owners utilize for business interests, and social space, which people use to live and do activities. This study aims to evaluate the effectiveness of street children handling policies through repressive and preventive approaches implemented by the Makassar City Government. This research uses a qualitative approach with a literature study method and descriptive-critical analysis. The theory of poverty and urbanization is used to explain that inequality is part of a capitalistic structure that places capital above people's social rights. The results show that government and community efforts in dealing with street children still face various structural barriers. Therefore, more inclusive and spatial justice-based policies are needed to solve this problem sustainably.